2020
DOI: 10.1097/scs.0000000000007075
|View full text |Cite
|
Sign up to set email alerts
|

Esthetic Repair of Facial Skin Defect After Resection of Malignant Tumor With Lateral Maxillocervical-Island Fasciocutaneous Flap

Abstract: excision of the lesion was performed. Tumor-free margins were established after wide excision which included the underlying perichondrium, resulting in a defect of 2.0 x 1.0 cm 2 with exposed bare cartilage.Turnover flap coverage was planned, and an extension skin incision 2 cm in length was made on the caudal portion of the defect area where the cephalic portion of earlobe is located (Fig. 1B). After the extension incision, a flap was designed and dissection was carried out through the subperichondrial layer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…At present, common donor sites for the skin flaps include the dorsum of the foot, the anterolateral thigh, and the lateral arm. However, the skin flaps are more bloated, and the survival rate of the skin flaps after repair is not impressive, which in turn poses a negative impact on both the recipient and the donor sites [ 4 6 ]. It has been reported that flaps from the medial aspect of the upper arm can be used to repair SST defects of the opisthenar, with desirable effectiveness [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…At present, common donor sites for the skin flaps include the dorsum of the foot, the anterolateral thigh, and the lateral arm. However, the skin flaps are more bloated, and the survival rate of the skin flaps after repair is not impressive, which in turn poses a negative impact on both the recipient and the donor sites [ 4 6 ]. It has been reported that flaps from the medial aspect of the upper arm can be used to repair SST defects of the opisthenar, with desirable effectiveness [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of scalp tumors is on the rise, in contrast to skin tumors in other areas. Only a small percentage (1% to 2%) of scalp tumors are malignant, and intracranial invasion by SCC is rare [9,10] . However, such an invasion is indicative of a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%